ROLE OF LITHUANIAN NATIONAL COURTS IN THE ARBITRAL PROCEEDINGS - Audzevičius, Ramūnas; Parchajev, Denis (Teisė, 2017)
Article analyses the interaction between Lithuanian courts and arbitration. It examines the contribution of adopted and proposed amendments to the Law on Commercial Arbitration, as well as Lithuanian case law to effectiveness of arbitration as a dispute resolution method and outlines distinctive trends and characteristics of Role of Lithuanian national courts in arbitration process.